PROFIL EQ KEPEMIMPINAN WANITA PEMIMPIN DI DAERAH ISTIMEWA YOGYAKARTA - ALIYAH RASYID BASWEDAN (Jurnal Kependidikan, 2004)
Abstract The main problems of this research are the women leader profile on their leadership in the social organization and how is the Woman Leadership EQ on doing their leadership. The objective of the research is to explore how the woman leaders implement their leadership and to explore their ability to organize: 1) personal awareness; 2) self-management 3) personal motivation; 4) empathy; 5) and how the educational level related to leadership EQ. in this research population is defined as sum and the typical individual who has similarities and to them the result will be suitable. Population on this research is women leader who involve on League of Woman Organization Coordination (BKOW) DIY they are representative of each organization member of BKOW DIY, in total of 47 persons. The technique of the sample taking is with purposing sampling. The data will be analyzed by using analysis percentage descriptive and cross tabulation. Overall the leadership EQ of the respondent shows that those who has  high EQ is 8.6%, the medium level is 87.2% and the low level is 4.2%.it shows that more than 95% of the leadership EQ on women leader who are become  respondent of the research is medium and high and the low level is less than 5%. There is no relation between education and leadership EQ. it means that those who have higher education don’t always have high leadership EQ. This might be caused whether he acts as a shelter or not. Keywords: Leadership, EQ